Assessing the Role of Parental Involvement Policies in Improving Early Childhood Education Outcomes in Indonesia - Maria Fernanda Oliveira; Joao Carlos Pereira; Ana Luiza da Silva (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article investigates the role of parental engagement policies in improving early childhood education (ECE) outcomes in Indonesia. Through a longitudinal analysis of ECE institutions and surveys with parents and teachers, the study highlights the impact of parental engagement on children’s cognitive and social development. Findings suggest that targeted policy measures to increase parental engagement contribute to improved educational outcomes, particularly in disadvantaged communities. The study advocates for policies that foster partnerships between parents and educators to support holistic child development.